FOOD AS A CRITICAL METAPHOR FOR GLOBALIZATION: SPAZIALIZATION OF TERRITORIAL IMBALANCES. EVIDENCE FROM THE GLOBAL SOUTH - Silvia IACUONE; Fabrizio FERRARI; Marina FUSCHI (Revista Română de Geografie Politică)
The purpose of this paper is to represent the spatialisation of the geography of hunger at the national level, taking as its starting point the most alarming situations denoted by the Global Hunger Index (GHI). After identifying the countries that persist in the most severe conditions of food insecurity, the causes that most influence these situations are highlighted, also through the use of specific indicators. Globalisation not only brings the benefit of a global approach to issues of universal solidarity (albeit still feeble in its concrete effects), but also many issues that aggravate the already difficult local situations.